A systematic review of applied theatre practice in the Indian context of mental health, resilience and wellbeing. Issue 2 (1st December 2019) - Crossley, Mark; Barrett, Andy; Brown, Brian J.; Coope, Jonathan; Raghaven, Raghu
AbstractThis systematic review seeks to evaluate the documented uses of applied theatre practice within an Indian context. For the purposes of this review, specific applied theatre practices were focused upon, notably community theatre, theatre in education, theatre in health education and Theatre for Development. This article was written in preparation for a collaborative research project (http://mhri-project.org ) utilizing community theatre practices to investigate mental health and resilience within slum (basti) communities in the city of Pune, in the state of Maharashtra in India. At its most particular level, the review focuses on theatre interventions within migrant slum communities. Of specific interest is the conjunction of applied theatre with research and practice in mental health and wellbeing, and how such collaborations have investigated levels and modes of mental resilience within migrant communities. The review also draws upon related global research to contextualize and inform the Indian context. At present, systematic reviews are not prevalent within the research fields of theatre generally or applied theatre specifically, yet these reviews arguably offer the breadth of objective evidence required to interrogate the efficacy of this practice. This review is therefore intended to rigorously map the existing academic research and the more diffuse online dialogues within India that are pertinent to the subject; to consider the relations, contradictions, absences and inconsistencies within this literature; and, from this, to articulate key findings that may be integrated into the planning and delivery of new initiatives within this field.